2020
DOI: 10.1038/s41598-020-72324-9
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, distribution, and health risk assessment of quinolone antibiotics in water, sediment, and fish species of Qingshitan reservoir, South China

Abstract: The residual antibiotics in the environment have lately caused widespread concerns. However, little information is available on the antibiotic bioaccumulation and its health risk in drinking water resources of South China. Therefore, the occurrence, distribution, and health risk of four quinolone antibiotics including ofloxacin (OFX), norfloxacin (NOR), ciprofloxacin (CIP), and enrofloxacin (ENR) in the Qingshitan reservoir using high-performance liquid chromatography were investigated. Results revealed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 32 publications
0
37
0
1
Order By: Relevance
“…Quinolone concentrations in meat, water and environmental samples exceed this threshold by some margin in a number of countries, but especially so in certain Asian countries. For example, studies have found that the mean concentration of ciprofloxacin in samples of milk, eggs, and edible fish in China to be 8.5 µg/L, 16.8 µg/kg and 331.7 µg/kg, respectively, [28][29][30]. The ingestion of these relatively high concentrations of quinolones in food products was the favoured explanation for the the high median concentration of quinolones (median 20 µg/kg), found in the colons of the general human population in 3 regions of China [31].…”
Section: Discussionmentioning
confidence: 99%
“…Quinolone concentrations in meat, water and environmental samples exceed this threshold by some margin in a number of countries, but especially so in certain Asian countries. For example, studies have found that the mean concentration of ciprofloxacin in samples of milk, eggs, and edible fish in China to be 8.5 µg/L, 16.8 µg/kg and 331.7 µg/kg, respectively, [28][29][30]. The ingestion of these relatively high concentrations of quinolones in food products was the favoured explanation for the the high median concentration of quinolones (median 20 µg/kg), found in the colons of the general human population in 3 regions of China [31].…”
Section: Discussionmentioning
confidence: 99%
“…Quinolone concentrations in meat, water and environmental samples exceed this threshold by some margin in a number of countries, but especially so in certain Asian countries. For example, studies have found that the mean concentration of ciprofloxacin in samples of milk, eggs, and edible fish in China to be 8.5 μg/L, 16.8 μg/kg and 331.7 μg/kg respectively [28][29][30]. The ingestion of these relatively high concentrations of quinolones in food products was the favoured explanation for the the high median concentration of quinolones (median 20 μg/kg), found in the colons of the general human population in 3 regions of China [31].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, different reports indicate that the characteristics of the soil (pH, salinity and temperature) influence the adsorption of FQs in sediments [ 299 , 300 , 304 ]. Huang et al, determined the concentrations of FQs from different environmental sources, finding that detected FQs concentrations represent a risk for human health and the environment [ 305 ].…”
Section: Impact Of Quinolones In the Environmentmentioning
confidence: 99%